Accelerating dermal wound healing and mitigating excessive scar formation using LBL modified nanofibrous mats. (5th January 2020) - Wu, Guomin; Ma, Xiao; Fan, Le; Gao, Yuying; Deng, Hongbing; Wang, Yining
Abstract: Developing an ideal wound dressing material which could accelerate wound closure and achieve scarless wound healing was the ultimate goal of numerous researchers. In this study, biomimetic silk fibroin (SF)/polycaprolactone (PCL) matrices were fabricated via co-electrospinning and positively charged chitosan (CS) and negatively charged type I collagen (COL) were deposited on the nanofibrous mats through electrostatic layer-by-layer (LBL) self-assembly technique. Scanning electron microscopy images indicate that the average fiber diameter of SF/PCL nanofibers became larger and more and more irregular protuberances were observed on their surfaces with the LBL process. Besides, the chemical structure and composition investigation further verified the successful deposition of CS/COL. Additionally, tensile strength and water contact angle tests showed the LBL modified mats had enhanced mechanical properties and good hydrophilicity. Moreover, LBL structured mats acquired excellent antibacterial activity and better ability to promote cell attachment, growth and proliferation. Ultimately, in vivo wound healing assay in rat models revealed that LBL structured mats could reduce the wound closure time, increase collagen production and mitigate excessive scar formation through TGF-β/Smad signaling pathways, which demonstrated the potential application of the nanofibrous mats in skin regeneration. Graphical abstract: Image 1 Highlights: Chitosan/collagen was coated on Silk fibroin/Polycaprolactone nanofibrous mats. The modified mats achieved excellent antibacterial activity and cytocompatibility. The modified mats accelerated skin wound healing and mitigated scar formation. The modified mats regulated Transforming Growth Factor-β/Smad signaling pathways.